PP-015 Release of acyclovir from liposomes: An in vitro study. (14th February 2016) - Coppolino, S; Federico, F; Di Perna, F
Abstract : Background: Liposomes are small spherical artificial vesicles that can be created from cholesterol and natural non-toxic phospholipids and are used as carriers to deliver a broad range of drugs. Acyclovir, known for its antiviral activity, has poor oral bioavailability requiring frequent dosing regimens. For this reason, alternative delivery approaches are required to increase the therapeutic potential of this drug. Purpose: The aim of this work was to formulate an extented release suspension of acyclovir using liposomes. Material and methods: Liposomes were prepared by using weighed amounts of soya lecithin and cholesterol dissolved in chloroform. The mixture was placed in a rotary vacuum evaporator fitted with a water circulating bath. The temperature of the water was set at 32°C to evaporate the solvent. After evaporation, the flask was kept in a vacuum dessicator overnight for complete removal of residual chloroform. Acyclovir (1.66 mg/mL) was dissolved in phosphate buffer (pH 7.4) and the desidered volume was taken into a flask containing lipid film. The film was hydrated in a rotary vacuum evaporator mantained at 60°C and rotated until the lipid film was dispersed in the aqueous phase. The sizes of the vesicles were reduced by a bath sonicator at 60°C for 1 h. After sonication, the preparation was kept at room temperature for 1 h for vesicle formation and then at 4°C in an inert atmosphere for 24 h. The preparation was then centrifuged at 5000 rpm at 4°C for 5 min. The supernatant containing vesicles was taken as a suspended formulation. The morphology of the vesicles was performed by scanning electron microscope. In vitro release of acyclovir from liposomes was conducted by dialysis in a dialysis sac with 180 mL of phospate buffer at 32°C stirring at 300 rpm. At 5 min intervals, an aliquot of liposome suspension was taken and subjected to HPLC analysis at a wavelenght of 252 nm. Data were subjected to ANOVA followed by the Studentised range test using the software Statistica. Results: It was found that about 90% release of drug was obtained in 150 min. Conclusion: The results suggest that acyclovir was released for a prolonged period of time from liposomes. Further studies regarding in vivo experiments for toxicity and efficacy are warranted. No conflict of interest.